Induction immunosuppression and the risk of incident malignancies among older and younger kidney transplant recipients: A prospective cohort study. Issue 12 (20th November 2020) - Wang, Lingyu; Motter, Jennifer; Bae, Sunjae; Ahn, JiYoon B.; Kanakry, Jennifer A.; Jackson, John; Schnitzler, Mark A.; Hess, Gregory; Lentine, Krista L.; Stuart, Elizabeth A.; Segev, Dorry L.; McAdams‐DeMarco, Mara
Abstract: Background: Older (≥65) KT recipients differ from their younger counterparts in their immune response to immunosuppression (IS) and may have a different risk of malignancy after receiving induction. Methods: We identified 66 700 adult KT recipients treated with anti‐thymocyte globulin (ATG) ( n = 40 443) or interleukin‐2 receptor antagonist (IL‐2RA) ( n = 26 327) induction (1/1/1999–12/31/2014) using USRDS/Medicare data. We estimated the risk of first‐diagnosed post‐KT malignancy associated with induction (ATG vs. IL‐2RA) using Cox proportional hazard models. We then tested whether these risks differed between older and younger recipients (Wald test for interaction). Models incorporated inverse probability of treatment weights to adjust for confounders. Results: The 3‐year cumulative incidences of any diagnosed malignancy were 11.5%. ATG was associated with a higher malignancy risk (HR = 1.12, 95%CI:1.06–1.18). This association differed ( pinteraction = 0.04) between younger (HR = 1.12, 95%CI:1.06–1.18) and older recipients (HR = 1.03, 95%CI:0.96–1.09). ATG was also associated with higher risk of skin (HR = 1.18, 95%CI:1.08–1.29), lung (HR = 1.24, 95%CI:1.05–1.47), and ovary malignancies (HR = 1.94, 95%CI:1.08–3.48). However, only the association of ATG with post‐KT skin malignancy differed ( pinteraction = 0.01) between younger (HR = 1.18; 95%CI:1.08–1.29) and older (HR = 1.01; 95%CI:0.93–1.09) recipients. Conclusions: Compared with IL‐2RA induction, ATG was associated with elevated post‐KT malignancy risk but only among younger recipients. Transplant centers may need to tailor induction IS for younger recipients to mitigate malignancy risk.